Directional diagrams of acoustic radiation from unmanned aerial vehicles - Kartashov, V.M.; Oleynikov, V.M.; Seleznyov, I.S.; Kartashov , O.V. (Radiotekhnika, 2022)
When solving the urgent task of detecting small unmanned aerial vehicles (UAVs) by their acoustic radiation (AR), there is a need to study the AR characteristics of UAVs. Therefore, considerable attention is paid in the literature to theoretical and experimental studies of the structure and parameters of the sound field created by UAVs. This article is devoted to the experimental study of the directional diagrams of the acoustic radiation from the DJI Phantom 3 unmanned aerial vehicle. The UAV AR recording experiment was conducted in a "silenced" chamber, the walls of which are covered with sound-absorbing panels with a surface of a special geometric shape. The experimental setup includes the UAV mounted on a boom, a microphone for sound recording, and a boom for the microphone. Studies of the structure and parameters of the sound field of the quadcopter have shown that the spectra of the emitted signal have pronounced harmonic components with frequencies multiples of the propeller rotation frequency. The spectral components have the greatest power in the frequency range up to 500 Hz, where the first harmonic has the largest amplitude, and then the spectrum components decrease to the ambient noise level. Obtained two-dimensional and three-dimensional directional diagrams of the UAV AR with and without propellers when only the aircraft engine is operating. It is shown that in the absence of screws, the acoustic radiation is much weaker in level. The experimental data was also presented in the form of three-dimensional AR diagrams for the four harmonics of the acoustic signal, and it was analyzed what changes in the spatial orientation of the UAV AR are observed based on changes in the three-dimensional figure for each of the radiation harmonics. It is shown that the spatial distribution of both the total energy (over the entire frequency range) of the acoustic signal and the energy of its individual spectral (harmonic) components is significantly anisotropic. It follows from this conclusion that the range of UAV detection and observation in real conditions is a statistical value that depends on the angle of its observation.